Embracing New Perspectives in History, Social Sciences, and Education: Proceedings of the International Conference on History, Social Sciences, and Education (ICHSE 2021), Malang, Indonesia, 11 September 2021 - Ronal Ridhoi; Arif Subekti; Francis M. Navarro (Routledge, 2023)
This book provides a collection of articles resulting from the International Conference on History, Social Sciences, and Education (ICHSE), which was held on 11 September 2021. The Department of History of Malang State University choose "Embracing New Perspectives in History, Social Sciences, and Education" as the main topic, and elaborates on five subthemes: 1) new trends in historical research; 2) formulation of new perspectives in history, social sciences, and education; 3) transdisciplinary research in history, social sciences, and education; 4) innovations in historical and social science learning during pandemics; 5) New ideas in the research and practice of social sciences and education. This seminar was open to international academics. This book presents new perspectives on methodology, methods, theory, and themes on history, social sciences, and education research from various perspectives on methodology and historiography. Now, history is not only about politics, economy and military, but also about environment, social, education, culinary, and so on. This book will be useful for students, historians, and the general public, in recording the development of Indonesian historical writing perspectives.
Keywords: 900; methodology; tourism; transdisciplinary research